Cream Soup Instan Substitusi Tepung Cangkang Udang dalam Upaya Meningkatkan Kadar Kalsium sebagai Selingan MP-ASI: Instant Cream Soup with Shrimp Shell Flour Substitution to Increase Calcium Levels for A Weaning Food - Bella, Shinta; Wiranda, Yosva; Ilhamy, Fitri Aidina; Firdaus, Firdaus (Jurnal Ilmu Gizi dan Dietetik, 2024)
Stunting is a condition of chronic malnutrition caused by inadequate nutritional intake over a long period of time due to the provision of food that does not meet nutritional needs. One way that can be done to prevent stunting is through food fortification. Food fortification that can be carried out includes the use of shrimp raw materials by using their shells. Shrimp shells are known to contain high levels of calcium which is good for the growth and development of children. The research aims to determine the sensory quality characteristics and nutritional content of instant cream soup products with the addition of shrimp shell flour. The experimental study used a Completely Randomized Design (CRD). The design consisted of 4 treatments with the ratios F0 (100% wheat flour:0% shrimp shell flour), F1 (75% wheat flour:25% shrimp shell flour), F2 (50% wheat flour:50% shrimp shell flour), F3 (25% wheat flour:75% shrimp shell flour). Statistical tests were used to analyze the data, including the Kolmogorov-Smirnov test to assess the normality of the data and the Kruskal Wallis test to compare the treatments. The best formulation selected was F3 which has hedonic qualities, namely a slightly yellow color, a pleasant and not fragrant aroma, a slightly thick texture, and a slightly savory taste. The nutritional content of F3 instant cream soup includes water content 7.26%, ash 8.64%, protein 15.35%, fat 24.43%, carbohydrates 44.32% and calcium 54.39%.